2008
DOI: 10.1371/journal.pntd.0000222
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Natural Populations of Human and Rodent Schistosomes in the Lake Victoria Region of Kenya: A Molecular Epidemiological Approach

Abstract: Background Schistosoma mansoni exists in a complex environmental milieu that may select for significant evolutionary changes in this species. In Kenya, the sympatric distribution of S. mansoni with S. rodhaini potentially influences the epidemiology, ecology, and evolutionary biology of both species, because they infect the same species of snail and mammalian hosts and are capable of hybridization.Methodology/Principal FindingsOver a 2-year period, using a molecular epidemiological approach, we examined spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 53 publications
8
88
0
1
Order By: Relevance
“…Indeed, experiments by Kagan and Geiger (1965) and File (1975) showed that when B. glabrata already shedding S. mansoni cercariae were later exposed to additional miracidia, some of these miracidia were able to develop and produce cercariae. Microsatellite and Southern blot studies have shown that field-collected Biomphalaria snails, including B. glabrata , are not uncommonly shedding cercariae of multiple genotypes, with as many as 8 genotypes reported from one snail (Minchella et al, 1995; Steinauer et al, 2008). The overall results suggest that the underlying interactions of echinostomes and schistosomes with B. glabrata differ, with it easier to evoke acquired resistance in the case of echinostomes, possibly because B. glabrata is more prone to develop age-related resistance to echinostomes than to schistosomes.…”
Section: Acquired Resistance Of Snails To Digenean Infection: Anotmentioning
confidence: 99%
“…Indeed, experiments by Kagan and Geiger (1965) and File (1975) showed that when B. glabrata already shedding S. mansoni cercariae were later exposed to additional miracidia, some of these miracidia were able to develop and produce cercariae. Microsatellite and Southern blot studies have shown that field-collected Biomphalaria snails, including B. glabrata , are not uncommonly shedding cercariae of multiple genotypes, with as many as 8 genotypes reported from one snail (Minchella et al, 1995; Steinauer et al, 2008). The overall results suggest that the underlying interactions of echinostomes and schistosomes with B. glabrata differ, with it easier to evoke acquired resistance in the case of echinostomes, possibly because B. glabrata is more prone to develop age-related resistance to echinostomes than to schistosomes.…”
Section: Acquired Resistance Of Snails To Digenean Infection: Anotmentioning
confidence: 99%
“…After 3-4 hours (Steinauer et al, 2008), each well was examined for the presence of cercariae under a stereo microscope (magnification: 12-25 x). All cercariae found were transferred onto a slide, inspected with a compound microscope (magnification: 4x /0.10 and 10x /0.25) and identified by the morphological characteristics using the identification key of Frandsen and Christensen (1984).…”
Section: Samplingmentioning
confidence: 99%
“…Schistosomes differ with respect to the time of day they emerge from their snail hosts, with some species emerging predictably at night ( Schistosomatium douthitti ), early morning ( Schistosoma rodhaini ), midday ( S. mansoni ), later in the afternoon ( S. japonicum ), and some throughout the day ( T. physellae ). Time of cercarial release has been well investigated relative to behavioral patterns of known definitive hosts [42, 43]. …”
Section: Diversity Of Cercarial Body Form and Behaviormentioning
confidence: 99%